Pengaruh Antara Pola Asuh Permisif Terhadap Kecerdasan Emosi Pada Siswa Kelas X SMK Negeri 9 Samarinda. - Wahyuni, Emy Nur (MOTIVASI, 2014)
This study aims to determine whether there is a significant influence of permissive parenting on emotional intelligence of students grade 9 SMKN Samarinda. In this study, the independent variable is permissive parenting, while the dependent variable is emotional intelligence. The hypothesis is "there is an influence of the Permissive Parenting on Emotional Intelligence". This study was addressed to students grade 9 and surveyed 185 students SMKN Samarinda. This study used the probability sampling. Data analysis technique used corelations product moment analysis. The results showed that there wasa significant influence of permissive parenting on emotional intelligence with R2 = 0.023, and p = 0.037 <0.05. However coeficient correlative showed negative correlation (R=-0.135) which means the two variables inversely related (the increasing of in one variable will be accompanied by the decreasing in the other variable). In this study it can be concluded that the more higher of permissive parentingthe more lower emotional intelligence ofÂ  students grade 9 SMKN Samarinda.